Makna Simbolik Sesaji dalam Selamatan Tingkeban di Desa Karanganom Kabupaten Trenggalek - Febrianti Dewi, Monica; Sumarlam (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2024)
Tingkeban celebration is a culture of commemorating pregnancy at the age of seven months. In the tingkeban celebration, there are offerings that contain implicit meanings. The meaning of these offerings can be done symbolically by exploring the symbols in them. Therefore, this study aims to describe the symbolic meaning of offerings in tingkeban celebrations in Karanganom Village, Trenggalek Regency. This study includes qualitative research by applying an ethnographic approach. The data sources for this research are from events, informants as many as three native residents of Karanganom Village, Trenggalek Regency, and library sources that support this research. The data for this research are the names of offerings and their symbolic meanings contained in the tingkeban celebration in Karanganom Village, Trenggalek Regency. Data was collected through observation and structured interviews using the skill and listening method. Next, the data was analyzed using ethnographic methods. The results of this research show that there are 25 names of offerings in the tingkeban celebration in Karanganom Village, Trenggalek Regency and they can be divided into three categories, namely food, flowers and drinks. Each of these offerings contains an implicit meaning in it which is a symbol of the tingkeban safety offerings in Karanganom Village, Trenggalek Regency. The implied meaning in it also reflects the mindset of the local community which is closely related to the hopes and symbols for pregnant women and unborn babies and human life.